Effectiveness of Cognitive Restructuring Technique to Reduce Students' Verbal Aggression - Yunita Dwi Setyoningsih; Parwati Parwati; Riski Putra Ayu Distira; Yanuari Srianturi (Ma'soem University, 2024)
This study aims to determine the effectiveness of individual counseling using cognitive restructuring techniques to reduce students' verbal aggression. This research method is pre-experiment with one group pretest-posttest design. The subjects of this study were students of class VIII (eight) MTs Islamiyah Malo in the 2022-2023 academic year. While the sample taken was 3 students with a purposive sampling technique. Data collection used verbal aggression instruments, observations and interviews. The results of this study indicate that the verbal aggression behavior of class VIII (eight) MTs Islamiyah Malo students before and after being given treatment with cognitive restructuring techniques is effective in reducing verbal aggression of DCP students 92% in the high category after being given to 66% in the moderate category, ACK students 79% in the high category after being given to 64% in the moderate category, AMA students 81% in the high category after being given to 61% in the moderate category. Data analysis based on the results of the paired sample t-test shows the sig value. (2 tables) of 0.020 < 0.05, then Ho is rejected and Ha is accepted, which means there is a significant difference, thus meaning that individual counseling services using the cognitive behavior therapy approach with cognitive restructuring techniques are effective in reducing verbal aggression of students at MTs Islamiyah Malo.